Nurses support in reducing working stress among medical doctors in public hospitals: conceptualizing job demands-resources model / Nor Farehan Omar and Aizzat Mohd Nasurdin - Omar, Nor Farehan; Mohd Nasurdin, Aizzat (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, Malaysia, 2019)
The last two decades of research in social and health psychology have established the cohesive of nurses support to promote good mental health and physical health among medical doctors. Although it is commonly assumed that nurses support positively predicts the good health status of medical doctors, the literature are still lacking in focusing the roles of nurses towards medical doctors in hospitals. This conceptual paper suggests how nurses support are associated with reducing prolonged stress among medical doctors in public hospitals which include to determine their health status due to lack of access to supportive workplace. The Job Demands-Resources Model and Conservation of Resource (COR) Theory serve as the foundation in developing the proposed research model. Job burnout is proposed as a mediator in the above-mentioned relationship.